Peningkatan Hasil Belajar IPAS Menggunakan Model Kooperatif Learning Tipe Team Games Tournament Berbantuan Quiziiz bagi Peserta Didik Kelas V SDN 01 Rejang Lebong - Frayoga, Andre; Desyandri, Desyandri (Asian Journal of Early Childhood and Elementary Education, 2025)
This study was motivated by the low learning outcomes of students because teachers have not used learning models that can encourage participation, active collaboration and meaningful learning for students. The purpose of this study was to describe the improvement of students' learning outcomes in IPAS learning by using the Team Games Tournament (TGT) type cooperative learning model assisted by Quiziiz in class V SDN 01 Rejang Lebong. This research is a classroom action research (PTK) that uses qualitative and quantitative approaches. This research was conducted in two cycles, namely cycle I which consisted of 2 meetings and cycle II which consisted of 1 meeting. Each cycle consisted of four stages, namely planning, implementation, observation, and reflection. The subjects of this research were teachers and 30 fifth grade students of SDN 01 Rejang Lebong. The data of this study were obtained from the results of the teaching module assessment, implementation process, and learning outcomes. The results showed an increase from cycle I to cycle II. The increase in research results is on: a) teaching module cycle I was 89.8 (Good) and increased in cycle II to 95.8% (very good), b) Implementation in the aspect of the teacher cycle I was 86.7% (good) and increased in cycle II to 94.4% (Very Good), in the aspect of students cycle I was 83.25% (Good) and increased in cycle II to 95.2% (very good), c) Learning outcomes of students cycle I was 81% (Good) and increased in cycle II to 88.7% (Good). Based on these results, it can be concluded that using the cooperative learning model of Team Games Tournament type assisted by quizizz for class V students of SDN 01 Rejang is able to actively involve students, increase collaboration and cooperation of students in groups, create a meaningful learning atmosphere, train critical thinking and increase curiosity and confidence of students in the learning process, so as to improve student learning outcomes in learning.